Effects of Aerobic Exercise on Some Hematological Parameters in Healthy Athletic Subjects in Umuahia - Nwokocha, Maureen Njideka (International Journal of Membrane Science and Technology, 2023)
There is an accord that exercise induces changes in hematological parameters. But there are conflicting findings on the direction of those changes. The aim of this study is to highlight the consequences of aerobics on some hematological parameters in healthy athletic subjects in Umuahia. It focuses on how to determine the effect of aerobic exercise on some hematological parameters such as, white blood cell, red blood cell, neutrophil, lymphocyte, platelet etc. The subjects consist of 10 males and 1 female healthy athlete. Subjects were selected after they were informed of the experimental details and the participants gave their consent to participate in the study. The result of the analysis showed that the effect of aerobic exercise on some hematological parameters increases after the exercise in most of the hematological parameters except for mean corpuscular hemoglobin that decreases after a moderate aerobic exercise.